Dependence of the mechanical fracture energy of the polymeric composite material from the mixture of filler fractions - E. M. Nurullaev; A. S. Ermilov (Fracture and Structural Integrity, 2014)
This paper for the first time presents an equation for calculating the mechanical fracture energy of the polymeric composite material (PCM) with regard to the basic formulation parameters. By means of the developed computer program the authors calculated the mechanical fracture energy of the polymer binder of the 3D cross-linked plasticized elastomer filled with multifractional silica. The solution of the integral equation was implemented using the corresponding dependence of stress on relative elongation at uniaxial tension. Engineering application of the theory was considered with respect to asphalt road covering. The authors proposed a generalized dependence of ruptural deformation of the polymer binder from the effective concentration of chemical and physical (intermolecular) bonds for calculating the mechanical fracture energy of available and advanced PCMs as filled elastomers.